2002
DOI: 10.1038/ni818
|View full text |Cite
|
Sign up to set email alerts
|

K3-mediated evasion of CD8+ T cells aids amplification of a latent γ-herpesvirus

Abstract: The murine gamma-herpesvirus-68 (MHV-68) K3 protein, like that of the Kaposi's sarcoma associated herpesvirus, down-regulates major histocompatibility complex (MHC) class I expression. However, how this contributes to viral replication in vivo is unclear. After intranasal MHV-68 infection, K3 was transcribed both during acute lytic infection in the lung and during latency establishment in lymphoid tissue. K3-deficient viruses were not cleared more rapidly from the lung, but the number of latently infected sple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
154
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(159 citation statements)
references
References 38 publications
4
154
1
Order By: Relevance
“…This idea emerged from an experiment, which was performed using genetically modified murine ␥-herpesvirus 68 (13). First, an mK3-deficient virus, which is not able to down-regulate MHC I expression efficiently, was generated.…”
Section: Inhibition Of Mhc Class II Expression and Immune Responses Bmentioning
confidence: 99%
“…This idea emerged from an experiment, which was performed using genetically modified murine ␥-herpesvirus 68 (13). First, an mK3-deficient virus, which is not able to down-regulate MHC I expression efficiently, was generated.…”
Section: Inhibition Of Mhc Class II Expression and Immune Responses Bmentioning
confidence: 99%
“…In the C57BL/6 background, IFN-g receptor 2/2 mice challenged with MuHV-68 maintained a progressive interstitial fibrosis that did not resolve, which could be the result of reactivation of latent virus causing renewed infection and a continuation of the chronicity of the fibrotic response (26). (27); M11, a Bcl-2 homolog (28); ORF4, a complement-regulatory protein (29); M3, a highly secreted chemokine-binding protein (30,31); and ORF74, a G protein-coupled receptor (vGPCR) with sequence homology to chemokine receptor CXCR2 (32). Previous studies have shown that both the chemokine-binding protein and vGPCR play a prominent role in the chronic aspect of the infectious process (30)(31)(32).…”
Section: Experimental Models With An Altered Cytokine Phenotype Exhibmentioning
confidence: 99%
“…The MHV-68 K3 protein catalyzes the destruction of MHC class I heavy chains [27,28] and TAP [29], and is expressed in latently infected germinal center B cells [30], probably as part of a viral growth program. It reduces by approximately 90% the effectiveness of antiviral CD8 + T cells [31]. MHV-68 also evades CD8 + T cells during episome maintenance.…”
Section: Introductionmentioning
confidence: 99%